Ammonia Toxicity Induces Oxidative Stress, Inflammatory Response and Apoptosis in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) - Yan, Xiaobo; Chen, Yu; Dong, Xiaohui; Tan, Beiping; Liu, Hao; Zhang, Shuang; Chi, Shuyan; Yang, Qihui; Liu, Hongyu; Yang, Yuanzhi (Frontiers in Marine Science, 2021)
To study the effects of acute ammonia stress on the poisoning reaction of the hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu), 300 healthy grouper juveniles with an initial body weight of 51.4 ± 2.57 g were selected for an acute ammonia stress experiment using a half-lethal concentration of ammonia for 24 h, 48 h, 72 h, and 96 h with triplicate. The results show that 1) The half-lethal concentrations of ammonia for a hybrid grouper were 39.5 mg/L for 24 h, 27.3 mg/L for 48 h, 26.5 mg/L for 72 h, and 25.0 mg/L for 96 h, and the safe concentration was 2.50 mg/L. 2) The biochemical indices of the serum and livers of the groupers fluctuated under acute ammonia stress (P < 0.05), and the contents of serum cortisol and lactate reached the maximum value in 72 h (P < 0.05). 3) 24 h ammonia stress increased the activities of alkaline phosphatase, acid phosphatase, catalase, glutathione peroxidase, superoxide dismutase, lysozyme, and the content of immunoglobulin M in the liver (P < 0.05). Meanwhile, all ammonia-stressed fish groups had an increased amount of malondialdehyde in the liver (P < 0.05). 4) The ammonia poisoning caused significantly up-regulation of antioxidant genes , inflammatory cytokines and apoptosis genes (P < 0.05), and the expression of inflammatory cytokines and apoptosis genes were the highest in 24 h ammonia stress group. 5) The ammonia content in the water changed the abundance and evenness of intestinal microbes in the groupers, mainly in that ammonia stress significantly increased the relative abundance of fusobacteria, but significantly decreased the relative abundance of gemmatimonadetes (P < 0.05). It was speculated that apoptosis induced by ammonia poisoning in groupers may be related to oxidative stress and the activation of inflammatory factors, and excessive inflammatory stress may be one of the causes of ammonia poisoning in the hybrid grouper.